Effects of Anti-Nerve Growth Factor Antibody on Symptoms in the NC/Nga Mouse, an Atopic Dermatitis Model - Norikazu Takano; Takanobu Sakurai; Michio Kurachi (Elsevier, 2005)
Nerve growth factor (NGF) is an important substance in the skin, where it can modulate nerve maintenance and repair. However, the direct link between NGF and pruritic disease such as atopic dermatitis is not yet fully understood. To determine whether NGF plays a major role in atopic dermatitis and in the development or maintenance of skin lesions, we performed a study using NC/Nga mice and compared mice with and without skin lesions. Our examinations of the NC/Nga mice sought to detect nerve fibers in the epidermis, measured serum and skin NGF content, and observed skin NGF by immunohistochemistry staining. We also examined the effects of anti-NGF antibody on dermatitis symptoms in NC/Nga mice. In these mice, nerve fibers were significantly increased in the epidermis of lesioned skin, and the NGF content of the serum and skin was significantly elevated. Anti-NGF antibodies significantly inhibited the development and proliferation of skin lesions and epidermal innervation and significantly inhibited any growth in scratching but did not ameliorate scratching already developed. Our findings suggest that NGF plays important roles in the pathogenesis of atopic dermatitis-like skin lesions and that inhibiting the physiological effects of NGF or suppressing increased NGF production may prevent or even moderate the symptoms of atopic dermatitis. Keywords:: nerve growth factor (NGF), atopic dermatitis, NC/Nga mouse, anti-NGF antibody